Mucinousadenocarcinoma of the kidney presenting as chronic discharging sinus (Indian Journal of Case Reports, 2019)
Mucinous adenocarcinoma of the renal pelvis is a rare tumor constituting < 1 % of all tumors involving the kidney. We are presenting the case report of a 45-years-old female who presented with pus discharging sinus from the scar of previous surgery after 2 years of initial surgery. On CECT, the left kidney showed heterogeneous space-occupying lesion of size 10x6 cm. The patient underwent cytoreductive excision of mass followed by adjuvant radiotherapy. The patient was doing well and asymptomatic till 8 months of follow-up but after 8 months, she presented with recurrence and died after another 4 months. To our knowledge, none of the previous papers reported discharging sinus as a mode of presentation for mucinous adenocarcinoma of the kidney. The outcome of the patient with relevant literature is being discussed here.